Practical Guide to Exercise Physiology. 2nd Edition - Murray, R.; Kenney, W. L. (Human Kinetics, 2021)
Science comes to life with Practical Guide to Exercise Physiology, Second Edition. Taking an application-based approach, supported by vivid medical illustrations, this book provides students and health and fitness professionals with a simple and straightforward way to learn the fundamentals of human physiology, metabolism, and nutrition.